A comparison of lens parameters in patients with various subtypes of primary angle-closure disease and the normal population: A prospective study - Keya Chakrabarti; Swati Samant; Ramesh Mohapatra; Suchismita Mishra; Suprava Das; Meena Chakrabarti (Indian Journal of Ophthalmology, 2022)
Purpose: To assess the role of lens parameters in the detection and progression of primary angle-closure disease (PACD) by combining A-scan and A-scan optical coherence tomography (AS-OCT) parameters. Methods: A cross-sectional study was conducted in a tertiary health-care center in eastern India. A total of 91 study subjects including cases and controls were included in the study. The parameters studied were lens thickness (LT), lens axial factor (LAF), relative lens position (RLP), and lens vault (LV). Anterior chamber depth (ACD) and axial length (AL) were also analyzed using A-scan. Results: The LT was significantly more in all subtypes of PACD (from 4.24 ± 0.84 to 5.02 ± 0.18 mm) than in controls (4.04 ± 0.46 mm; P < 0.01). Similarly, LAF was significantly less among all subtypes of PACD compared to controls (P < 0.001). The RLP, calculated using the formula (ACD + 0.5 LT)/AL × 10, showed no significant difference (P > 0.05) between various study groups. The LV in acute angle-closure glaucoma (AcCG) patients was significantly higher compared to the control population (P < 0.01). Ocular parameters like ACD decreased, whereas LT and LAF increased from normal through primary angle closure (PAC) to primary angle-closure glaucoma (PACG). Logistic regression analysis found a significant association between a decrease in ACD and an increased risk of PACG (P-value was 0.0001) and an increase in LT and LAF with increased risk of PACG (P = 0.040 and P = 0.006, respectively). Conclusion: Inclusion of lens parameter assessment in the workup of a patient with PACD helps in detection and close monitoring of the progression from suspected to disease state.